2011
DOI: 10.1073/pnas.1108561108
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neural correlates of delay of gratification 40 years later

Abstract: We examined the neural basis of self-regulation in individuals from a cohort of preschoolers who performed the delay-ofgratification task 4 decades ago. Nearly 60 individuals, now in their mid-forties, were tested on "hot" and "cool" versions of a go/ nogo task to assess whether delay of gratification in childhood predicts impulse control abilities and sensitivity to alluring cues (happy faces). Individuals who were less able to delay gratification in preschool and consistently showed low self-control abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
393
1
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(420 citation statements)
references
References 48 publications
11
393
1
15
Order By: Relevance
“…Resistance to temptation (i.e., inhibitory control) is a relatively stable individual characteristic that predicts neural activation in fronto-striatal circuitries that integrate motivational and self-control processes [37]. Previous studies showed that preterm children have difficulties with inhibitory control [8] and that these predict later learning and attention problems [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to temptation (i.e., inhibitory control) is a relatively stable individual characteristic that predicts neural activation in fronto-striatal circuitries that integrate motivational and self-control processes [37]. Previous studies showed that preterm children have difficulties with inhibitory control [8] and that these predict later learning and attention problems [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is some indication that childhood EF may predict EF in adulthood. For instance, delay of gratification at the age of 4 y predicts cognitive control on a laboratory task 14 y later (44) and 40 y later (45), with evidence that individuals who had been less able to delay gratification as preschoolers showed less frontal activation and more activation of the ventral striatum when inhibiting motor responses to positive social cues 40 y later (45). Interventions aimed at promoting resilience in children living in adverse conditions by improving their EF would thus have the potential for long-term positive benefits, but they need to take note of these associations between early adversity and childhood EF.…”
Section: Discussionmentioning
confidence: 99%
“…The research by Casey et al (1) illustrates continuing stable differences in performance between individuals who were identified early in life as high or low delayers. It is now clear, however, that performance always reflects a combination of skill and motivation, ability and values, and top-down and bottom-up influences.…”
Section: Delay and Destinymentioning
confidence: 99%
“…Casey et al (1) suggest that what is stable is a biologically based ability to resist temptation-an ability subserved by the right inferior frontal gyrus-and that only the temptations themselves change with age: Candy is to the child as social affiliation is to the adult. This suggestion rests on the assumption that children who fail to wait for the larger reward are unable to do so.…”
Section: Values Vs Controlmentioning
confidence: 99%